Self-Acceptance for Mothers Who Have Children with Special Needs on Lower-Middle Socio-Economic Status in Bantul - Rosita Permatahati; Fx. Wahyu Widiantoro; Ayu Gigih Rizqia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Children with special needs are children who experience developmental delays either physically, psychologically, socially, or emotionally, and who have above-average abilities so that they need help that suits their needs to improve their abilities and quality of life. This study aims to find out the description of self-acceptance and the stages of self-acceptance of a mother who has a child with special needs with socioeconomic status with a middle to lower social status. The research method used is qualitative with a case study approach with several subjects 3. The data analysis methods used are reduction, data presentation, and conclusion drawn. The results of interviews and observations show that the three subjects have different self-acceptance, the middle to lower economy being one of the causes of different self-acceptance. The first subject has shown good acceptance, although sometimes they still feel dissatisfied in their efforts to achieve the recovery of children with special needs and resigned to their economic conditions. The second subject has been accepted, but the time is more used for work, so it is not optimal in accompanying children with special needs. The third subject with an unstable economy is still convinced that their needs can be met but still have difficulties in dealing with children with special needs. Anak berkebutuhan khusus merupakan anak yang mengalami keterlambatan perkembangan baik dari segi fisik, psikologis, sosial, atau emosional, dan yang mempunyai kemampuan diatas rata-rata sehingga mereka memerlukan bantuan yang sesuai dengan kebutuhannya untuk meningkatkan kemampuan dan kualitas hidupnya. Penelitian ini bertujuan untuk mengetahui gambaran penerimaan diri dan tahapan penerimaan diri seorang ibu yang mempunyai anak berkebutuhan khusus dengan status sosial ekonomi dengan status sosial menengah ke bawah. Metode penelitian yang digunakan yaitu kualitatif dengan pendekatan studi kasus dengan jumlah subjek 3. Adapun metode analisis data yang digunakan yaitu reduksi, penyajian data, dan penarikan Kesimpulan. Hasil dari wawancara dan observasi menunjukkan bahwa ketiga subjek memiliki penerimaan diri yang berbeda, ekonomi menengah ke bawah menjadi salah satu penyebab berbedanya penerimaan diri. Subjek pertama sudah menunjukkan penerimaan yang baik, walaupun terkadang masih merasa kurang puas dalam usaha mencapai kesembuhan anak berkebutuhan khususnya dan pasrah terhadap kondisi ekonominya. Subjek kedua sudah menerima, akan tetapi waktunya lebih banyak digunakan untuk bekerja, sehingga kurang maksimal dalam mendampingi anak berkebutuhan khususnya. Subjek ketiga dengan ekonomi belum stabil tetap yakin kebutuhannya bisa terpenuhi, tetapi masih kesulitan dalam menangani anak berkebutuhan khususnya.